Technology as a driver for new business logic. - Rockstrom, A.
Today's change in telecom business structure and logic is primarily driven by new datacom technologies. As network structures and cost topologies are in many respects turned upside down, so the business structure will be. One conclusion is that since access is the stronghold of the new technologies, there is a strong local advantage. This means that we will move toward a business arena in which bundling and value chains as we know them today are dead concepts; there will be strict separation of infrastructure and services, and numerous other changes that basically are the opposites of what we are used to today.
Keywords: IP infrastructure; Internet; Business logic; Datacom technologies; Network cost topologies; Network structures; Services; Telecom business logic; Telecom business structure